Contested lands : Israel-Palestine, Kashmir, Bosnia, Cyprus, and Sri Lanka - Bose, Sumantra, 1968- (Harvard University Press, 2007)
The search for durable peace in lands torn by ethno-national conflict is among the most urgent issues shaping our global future. Looking at the recent and current peace processes in Israel-Palestine, Kashmir, Bosnia, Cyprus, and Sri Lanka Bose addresses the question of how peace can be made, and kept, between warring groups with seemingly incompatible claims.